A conceptual framework of the relationships between family functioning, alexithymia and emotional intelligence among early adolescents in Tehran-Iran - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
Emotional intelligence structure is a concept with little empirical research, particularly in relation to the link between family circumstance and personality characters and with respect to gender, number of sibling, family income, and family educational status of early adolescents. In the present study, the researchers attempted to show that regarding to the definition and foundation of a conceptual framework how would design a conceptual framework according the relationships between family functioning, alexithymia and emotional intelligence variables, among Iranian early adolescents. Due to the lack of research on family functioning, alexithymia and their influences on early adolescents’ emotional intelligence in Iran, there is much need for research that explores those factors of influence on early adolescent’s emotional intelligence, specifically.